Tantangan dan Peluang ESG (Environmental, Social, and Governance) Reporting: Analisis Literatur tentang Peran Akuntansi dalam Pengukuran Kinerja Berkelanjutan Perusahaan - Mutiara N, Indah; Oktaria, Eka Travilta; Sari , Pipit Novila (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
ESG (Environmental, Social, and Governance) reporting has become a major focus in current business practices, playing a vital role in measuring companies' sustainable performance. This article aims to identify the challenges and opportunities in ESG reporting practices, with a specific emphasis on the role of accounting. Through comprehensive literature analysis, this study outlines various challenges faced in ESG reporting, including inconsistencies and standards, complexities in measuring environmental, social, and governance aspects, as well as increasing regulations and compliance related to ESG reporting. On the other hand, the research also identifies opportunities to enhance transparency, accountability, and sustainable performance of companies through ESG reporting practices. Stakeholder engagement, especially investors and consumers, is a critical factor in the success of ESG reporting practices. However, challenges remain in managing their expectations and needs effectively.